Examining the relationship between gender,age,education level and social cognitive factors in a health setting - Wee Yu Ghee; Md. Nor Othman; Sheau Fen Yap (2011)
Most research on exercise is dominated in the West and is seldom featured in the marketing literature. Efforts in examining the demographic differences with respect to social cognitive factors contained in the Theory of Planned Behavior (TPB) have been largely neglected. This paper aims to examine the relationship between gender, age, education level and the TPB sub-components of attitude, subjective norm, and perceived behavioral control. Conducted in Malaysia, this study employs a cross-sectional survey administered to a quota sample of 512 general adults. A fit measurement model with adequate evidence of convergent and discriminant validity is established using confirmatory factor analysis. Overall, the results show that gender, age, and education do exert a certain level of influence on the social cognitive factors and the subjects’ exercise behavior. The application of socio-cognitive approach to examine the exercise behavior yielded contributions in terms of theory, methodology, and practice.